Unspecified asthma, childhood-onset, and adult-onset asthma have different causal genes: a Mendelian randomization analysis - Zaied, Roan E.; Gokuladhas, Sreemol; Walker, Caroline; O’Sullivan, Justin M. (Frontiers in Immunology, 2024)
IntroductionAsthma is a heterogeneous condition that is characterized by reversible airway obstruction. Childhood-onset asthma (COA) and adult-onset asthma (AOA) are two prominent asthma subtypes, each with unique etiological factors and prognosis, which suggests the existence of both shared and distinct risk factors.MethodsHere, we employed a two-sample Mendelian randomization analysis to elucidate the causal association between genes within lung and whole-blood-specific gene regulatory networks (GRNs) and the development of unspecified asthma, COA, and AOA using the Wald ratio method. Lung and whole blood-specific GRNs, encompassing spatial eQTLs (instrumental variables) and their target genes (exposures), were utilized as exposure data. Genome-wide association studies for unspecified asthma, COA, and AOA were used as outcome data in this investigation. ResultsWe identified 101 genes that were causally linked to unspecified asthma, 39 genes causally associated with COA, and ten genes causally associated with AOA. Among the identified genes, 29 were shared across some, or all of the asthma subtypes. Of the identified causal genes, ORMDL3 had the strongest causal association with both unspecified asthma (OR: 1.49; 95% CI:1.42-1.57; p=7.30x10-51) and COA (OR: 3.37; 95% CI: 3.02-3.76; p=1.95x10-102), whereas PEBP1P3 had the strongest causal association with AOA (OR: 1.28; 95% CI: 1.16-1.41; p=0.007).DiscussionThis study identified shared and unique genetic factors causally associated with different asthma subtypes. In so doing, our study emphasizes the need to move beyond perceiving asthma as a singular condition to enable the development of therapeutic interventions that target sub-type specific causal genes.